Work Motivation Affecting Employees' Organizational Commitment of Gas Stations in Prachuap Khiri Khan Province - Limptiyakon, Panthip; Tuvadaratragool, Sumeth (Suan Dusit Graduate School Academic Journal, 2023)
The objectives of this research were 1) to study the level of organizational commitment of gas station employees in Prachuap Khiri Khan Province; 2) to study the level of work motivation of gas station employees in Prachuap Khiri Khan Province; and 3) to analyze the effect of work motivation on employees’ organizational commitment of gas stations in Prachuap Khiri Khan Province. This study was quantitative research. Population was gas station employees in Prachuap Khiri Khan Province and the sample size was 384 gas station employees. This research used questionnaire as a data collection tool with the reliability coefficient of 0.999 and IOC of 1 for each question. The purposive sampling technique was applied. Statistics used included mean, standard deviation, and multiple regressions. The results revealed that 1) the overall organizational commitment was found at the high level. When considering each aspect, behavioral commitment was found as the first rank, followed by attitudinal commitment and organizational determination of membership, respectively; 2) the overall work motivation was found at the high level. When considering each aspect, motivation factors come first, followed by maintenance factors; 3) Work motivation included motivation factors consisting of achievement, together with recognition, and maintenance factors consisting of salary, possibility of growth, company policies and administration. Job security affected organizational commitment of gas station employees in Prachuap Khiri Khan Province (82.80 percent) at the statistical significance level of 0.05.